Accuracy of preemptively constructed, Cone Beam CT‐, and CAD/CAM technology‐based, individual Root Analogue Implant technique: An in vitro pilot investigation. Issue 5 (21st December 2012) - Moin, David Anssari; Hassan, Bassam; Parsa, Azin; Mercelis, Peter; Wismeijer, Daniel
Abstract Objectives The aim of this in vitro pilot investigation is to assess the accuracy of the preemptive individually fabricated root analogue implant (RAI) based on three‐dimensional (3D) root surface models obtained from a cone beam computed tomography (CBCT) scan, computer‐aided designing (CAD), and computer‐aided manufacturing (CAM) technology and to measure the discrepancy in congruence with the alveolar socket subsequent to placement of the RAI. Materials and methods Eleven single‐rooted teeth from nine human cadaver mandibles were scanned with the 3D Accuitomo 170 CBCT system. The 3D surface reconstructions of the teeth acquired from the CBCT scans were used as input for fabrication of the RAIs in titanium using rapid manufacturing technology. The teeth were then carefully extracted. The teeth and RAIs were consequently optically scanned. The mandibles with the empty extraction sockets were scanned with CBCT using identical settings to the first scan. Finally, the preemptively made RAIs were implanted into their respective sockets, and the mandibles were again scanned with CBCT using the same scan settings as previous scans. All 3D surface reconstructions (CBCT 3D surface models and optical scan 3D models) were saved for further analysis. 3D models of original teeth and optical scans of the RAIs were superimposed onto each other; differences were quantified as root mean square (RMS) and Hausdorff surface distance. To obtain an estimate of the fit (congruence) of the RAIs in their respective sockets, the volumetric data sets of the sockets were compared with those of the root part of RAIs congruent with the sockets. Results Superimposed surfaces of the RAIs and the original tooth reveal discrepancy for RMS, volumetric geometry, and surface area varying from 0.08 mm to 0.35 mm, 0.1% to 7.9%, and 1.1% to 3.8%, respectively. Comparing volume differences of the alveolus with the socket corresponding part of the RAI resulted in every case the volume of the socket being greater than the root part of the RAI ranging from 0.6% to 5.9% volume difference. Conclusion The preemptive CAD/CAM‐based RAI technique might offer promising features for immediate implant placement. However, due to the lack of prospective clinical data, further research is needed to fine‐tune and evaluate this technique.